PERAN STRUKTUR ORGANISASI TERHADAP MOTIVASI KERJA KARYAWAN: TINJAUAN LITERATUR - Afera, Keyla Lena Theresita (PT Naureen Digital Education, 2025)
This literature review aims to analyze the role of organizational structure in influencing employee work motivation within industrial and organizational psychology. Using a descriptive qualitative approach, this study synthesizes findings from national and international journals indexed by SINTA and Scopus. The analysis focuses on identifying patterns in the relationship between structural characteristics such as decentralization, hierarchy, communication flow, and division of tasks and employee motivation. The findings show that a participative, flexible, and autonomy-supporting organizational structure positively contributes to motivation by fostering a sense of belonging, clarity of roles, and engagement. This paper contributes a theoretical perspective and practical recommendations for developing organizational designs that enhance psychological well-being and performance at work.